2021
DOI: 10.1111/beer.12347
|View full text |Cite
|
Sign up to set email alerts
|

CEO personality and language use in CSR reporting

Abstract: Chief executive officers (CEOs) hold the highest managerial authority in their enterprises. CEOs are responsible for overall organizational performance, which is influenced by their decisions. Recent business research has explored wide-ranging aspects of CEOs and their influence. Especially relevant to this study is research examining topics related to CEOs and corporate social responsibility such as the effects of CEO power and environmental, social, and governance disclosures on firm value (Li et al., 2018);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 105 publications
2
12
0
Order By: Relevance
“…It can thus be argued that individual differences play a relevant role in the creation and manifestation of CR. Personality in particular, has long been studied for its effect in several business fields, including marketing (Tan et al 2004 ), accounting and reporting (Marquez-Illescas et al 2019 ; Mahmoudian et al 2021 ), strategic decision-making (Hrazdil et al 2021 ), and entrepreneurship (Kraus et al 2018 ; Palmer et al 2019 ; Schulz and Flickinger 2020 ; Bellmann and Hübler 2022 ; Salmony and Kanbach 2022 ). Personality has also been used as an explanatory variable in several research studies (Choi and Hwang 2019 ; Clark et al 2020 ; Iqbal et al 2021 ; Jassem et al 2021 ; Maran et al 2022 ).…”
Section: Background Theories and Hypothesesmentioning
confidence: 99%
“…It can thus be argued that individual differences play a relevant role in the creation and manifestation of CR. Personality in particular, has long been studied for its effect in several business fields, including marketing (Tan et al 2004 ), accounting and reporting (Marquez-Illescas et al 2019 ; Mahmoudian et al 2021 ), strategic decision-making (Hrazdil et al 2021 ), and entrepreneurship (Kraus et al 2018 ; Palmer et al 2019 ; Schulz and Flickinger 2020 ; Bellmann and Hübler 2022 ; Salmony and Kanbach 2022 ). Personality has also been used as an explanatory variable in several research studies (Choi and Hwang 2019 ; Clark et al 2020 ; Iqbal et al 2021 ; Jassem et al 2021 ; Maran et al 2022 ).…”
Section: Background Theories and Hypothesesmentioning
confidence: 99%
“…Hrazdil et al (2020) validate that OCEAN traits obtained from IBM Watson are CEO specific and unrelated to firm characteristics, validate that CEO risk tolerance based on OCEAN varies with existing inherent and behavior-based measures for risk in predictable ways, and document a significant effect of inherent CEO risk tolerance on audit fees. Recent literature utilizes IBM Watson to obtain CEOs' Big Five traits to test their association with corporate social responsibility performance and reporting (Hrazdil et al 2021;Mahmoudian et al 2021).…”
Section: Research Modelmentioning
confidence: 99%
“…Wernicke et al (2021) revealed that CEOs can explain about 30% of the total variance in CSR initiatives and activities across firms. To date, research has explored how CEOs’ values, personalities, and demographic characteristics shape firms’ CSR practices (Boone et al, 2020; Mahmoudian et al, 2021; Tang et al, 2018; Walls & Berrone, 2017).…”
Section: Introductionmentioning
confidence: 99%